A simple robust method of synthesis of copper–silver core–shell nano-particle: evaluation of its structural and chemical properties with anticancer potency. (6th June 2018) - Banik, Milon; Patra, Mousumi; Dutta, Debanjan; Mukherjee, Riya; Basu, Tarakdas
Abstract: A simple method of synthesis of a stable bimetallic copper–silver nano-particle (CuAg-NP) was developed by successive reduction of Cu(NO3 )2 and AgNO3, using hydrazine hydrate as the reducing agent and gelatin and poly-vinyl pyrrolidone (PVP) as the capping agents. The round-shaped particles were of a core–shell structure with a core of Cu 0 atoms surrounded by a shell of Ag 0 atoms. The size and the mol. wt. of the NPs were (100 ± 10) nm and (820 ± 157) Kd, respectively; the particles were crystalline in nature and 90% of the precursors Cu(NO3 )2 and AgNO3 were converted to the NPs. The particles were more toxic to cancer cells than normal cells; the dose of the NPs (4–5 μ g ml −1 ), that killed about 75% of the different human cancer cell lines viz, HepG2 (liver cancer), A549 (lung cancer) and AGS (stomach cancer), killed only about 22.5% of the normal cell lines viz, WRL68 (liver) and WI38 (lung). Therefore, the NP may be developed as a potent anticancer drug in future. The more detailed study on the cytotoxicity of the CuAg-NP on the HepG2 cell line revealed that the particles caused cell cycle arrest in a G2/M phase, depolarization of mitochondrial membrane potential, translocation of phosphatidylserine residues from inner to outer leaflets of cell membrane and DNA degradation; these phenomena confirmed that the NP-induced cell death was apoptotic in nature.